Preparation method for plating zinc selenide substrate with DLC (Diamond Like Carbon) film layer
By plating the 251nmGe/211nmZnS/667.6nmGe dielectric layer on the zinc selenide substrate and combining with the DLC film layer, the problem of poor adhesion of the DLC film layer of the zinc selenide substrate is solved, and high adhesion and excellent transmittance are achieved. The film layer meets the requirements of use in harsh environments.
Patent Information
- Application Number
- CN202411781518.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-25
AI Technical Summary
The direct coating of zinc selenide substrate has poor adhesion and is difficult to meet the requirements for use in harsh environments.
The dielectric layer composed of 251nmGe/211nmZnS/667.6nmGe is used to base the dielectric layer. Through the combination of vacuum coating machine and carbon film machine, the DLC film layer of zinc selenide substrate is plated to improve the adhesion and transmittance of the film layer.
The high adhesion and excellent transmittance of the zinc selenide substrate DLC film layer are achieved, with an average transmittance of 8-12μm in the 8-12μm band, and passed the test of various harsh environments to meet the window film in various Requirements for use in harsh environments.
Smart Images

Figure CN119506788A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical coating, and more specifically to a method for preparing a DLC film layer coated on a zinc selenide substrate. Background Art
[0002] Zinc selenide (ZnSe) is a very good infrared material with a wide light transmission range, low absorption of infrared wavelengths, and can transmit visible light. It is a high-quality material for making infrared lenses, windows, output coupling mirrors and beam expanders. It can transmit from 0.5μm to 19μm, and has good imaging and thermal shock properties. Since zinc selenide lenses are used as windows, they must have the ability to operate normally for a long time in harsh environments, such as high-speed atmospheric flight, resistance to friction from foreign objects, resistance to rain immersion and corrosion in rainy and humid weather, etc. Diamond-like carbon (DLC) film solves these problems well, but the adhesion of DLC film directly plated on zinc selenide substrate is poor. Summary of the invention
[0003] In view of the problems existing in the background technology, an object of the present invention is to provide a method for preparing a DLC film layer plated on a zinc selenide substrate, wherein the prepared zinc selenide substrate accompanying coating sheet together with the film system containing the DLC film layer on the corresponding surface has an average single-sided transmittance greater than 77.5% in the 8-12μm band.
[0004] Another object of the present disclosure is to provide a method for preparing a DLC film layer plated on a zinc selenide substrate, wherein the prepared zinc selenide substrate and the film system containing the DLC film layer on the corresponding surface can meet the requirements of being used as a window piece in various harsh environments and meet the requirements of the application end.
[0005] Thus, a preparation method of a zinc selenide substrate coated with a DLC film layer comprises the following steps: S1, before coating, cleaning the accompanying plate of the zinc selenide substrate of the lens and the surface of the product on which the DLC film layer is to be coated; S2, placing the cleaned lens into a fixture, and hanging the fixture with the lens in place into the cavity of a vacuum coating machine, and setting the temperature of the cavity to 130°C; S3, starting the vacuum coating machine, evacuating the vacuum and heating the cavity, and the vacuum degree reaches 1.5×10 -3 Pa and the temperature of the chamber reaches the set temperature, the Hall ion source of the vacuum coating machine is turned on for cleaning. The cleaning time is 6 minutes. The anode voltage of the Hall ion source is 220V, the anode current is 1.2-1.5A, the neutralization current is 1.3-1.5A, the neutralization gas flow rate is 10sccm, and the argon gas flow rate accounts for 100%; S4, the vacuum degree reaches 1.0×10 -3Pa, a dielectric layer consisting of 251nmGe / 211nmZnS / 667.6nmGe is sequentially plated on the surface of the lens that needs to be plated with a DLC film, wherein the numbers with nm before Ge and ZnS are the thicknesses of the corresponding film layers, the Ge film layer is evaporated by electron beam evaporation, the ZnS film layer is evaporated by resistance heating, the deposition rate of the Ge film layer is 0.4nm / s, the deposition rate of the ZnS film layer is 0.6nm / s, and each film layer of the dielectric layer is deposited by ion source assistance and is deposited at the set temperature of the chamber; S5, after the dielectric layer is plated, the chamber is naturally cooled to below 80°C, and the fixture is taken out together with the lens; S6, the lens with the dielectric layer plated is taken out, and the smoothness of the dielectric layer of the product is checked; S7, the accompanying plated sheet and the product that has passed the smoothness test are placed on the bottom plate of the carbon film machine with the dielectric layer facing up; S8, the carbon film machine is evacuated to a vacuum of 1.2×10 -3 Pa, the carbon film machine starts to clean the RF ion source for 3 min, the argon flow rate of the RF ion source is 20 sccm, and the power is 600-700 W; S9, the vacuum of the carbon film machine reaches 8.0×10 -4 Pa starts to deposit the DLC film layer, the methane gas flow rate is 160sccm, the argon gas flow rate is 10sccm, the RF power supply power is 1000W, the deposition time is 3800s, and the thickness of the DLC film layer is 1200nm; S10, after the DLC film layer is deposited, the carbon film machine is cooled for 50-60min, and the door is opened to take out the lens.
[0006] The beneficial effects of the present disclosure are as follows: in the preparation method of the DLC film layer plated on the zinc selenide substrate according to the present disclosure, through steps S1 to S10, the 1200nm DLC film layer of the zinc selenide substrate is plated by priming with a dielectric layer composed of 251nmGe / 211nmZnS / 667.6nmGe. As verified by the test process, the accompanying plated sheet of the zinc selenide substrate together with the film system containing the DLC film layer on the corresponding surface (i.e., the dielectric layer plus the DLC film layer) can not only achieve an average single-sided transmittance of more than 77.5% (specifically 77.81%) in the 8-12μm band, but also pass the blister test, salt spray test, adhesion test, hot and cold shock test, constant temperature and humidity test, constant temperature and humidity test, friction resistance test (moderate friction test), low temperature test and high temperature test, so that it can meet the use of the window sheet in various harsh environments and meet the requirements of the application end. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 It is a schematic structural diagram of a zinc selenide substrate prepared according to the method for preparing a DLC film layer plated on a zinc selenide substrate disclosed in the present invention and a film system on a corresponding side.
[0008] Figure 2It is a transmittance curve diagram of the accompanying coating sheet of Example 1 together with the dielectric layer and the DLC film layer on the corresponding surface in the 8-12 μm band.
[0009] Figure 3 It is a photograph of the product of Example 1 together with the dielectric layer and the DLC film layer on the corresponding surface. DETAILED DESCRIPTION
[0010] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.
[0011] [Preparation method of DLC film layer plated on zinc selenide substrate]
[0012] Reference Figure 1 According to the present invention, the method for preparing a DLC film layer plated on a zinc selenide substrate comprises the following steps:
[0013] S1, before plating, clean the accompanying plating sheet as the zinc selenide substrate of the lens and the surface of the product that needs to be plated with DLC film;
[0014] S2, put the cleaned lens into the fixture, and hang the fixture with the lens into the cavity of the vacuum coating machine, and set the temperature of the cavity to 130℃;
[0015] S3, vacuum coating machine starts, vacuumizes and heats the cavity, and the vacuum degree reaches 1.5×10 -3 Pa and the temperature of the chamber reaches the set temperature, turn on the Hall ion source of the vacuum coating machine for cleaning. The cleaning time is 6 minutes. The anode voltage of the Hall ion source is 220V, the anode current is 1.2-1.5A, the neutralization current is 1.3-1.5A, the neutralization gas flow rate is 10sccm, and the argon gas flow rate accounts for 100%;
[0016] S4, vacuum degree reaches 1.0×10 -3 When the DLC film layer is deposited on the surface of the lens where the DLC film layer is required, a dielectric layer composed of 251nmGe / 211nmZnS / 667.6nmGe is deposited in sequence, wherein the numbers with nm before Ge and ZnS are the thicknesses of the corresponding film layers, the Ge film layer is evaporated by electron beam, the ZnS film layer is evaporated by resistance heating, the deposition rate of the Ge film layer is 0.4nm / s, the deposition rate of the ZnS film layer is 0.6nm / s, and each film layer of the dielectric layer is deposited by ion source assisted deposition and is deposited at the set temperature of the chamber;
[0017] S5, after the dielectric layer is plated, the cavity is naturally cooled to below 80°C, and the fixture and the lens are taken out;
[0018] S6, take out the lens coated with the dielectric layer and check the smoothness of the dielectric layer of the product;
[0019] S7, placing the accompanying plating sheet and the products that have passed the surface finish inspection on the bottom plate of the carbon film machine with the dielectric layer facing upward;
[0020] S8, carbon film machine vacuum reaches 1.2×10 -3 Pa, the carbon film machine starts to clean the RF ion source, the cleaning time is 3min, the argon flow rate of the RF ion source is 20sccm, and the power is 600-700W;
[0021] S9, carbon film machine vacuum reaches 8.0×10 -4 Pa started to deposit the DLC film, the methane gas flow rate was 160sccm, the argon gas flow rate was 10sccm, the RF power was 1000W, the deposition time was 3800s, and the thickness of the DLC film was 1200nm;
[0022] S10, after the DLC film coating is completed, the carbon film machine is cooled for 50-60 minutes, and the door is opened to take out the lens.
[0023] In the preparation method of the DLC film layer plated on the zinc selenide substrate according to the present disclosure, the 1200nm DLC film layer of the zinc selenide substrate is plated through steps S1 to S10 and the dielectric layer composed of 251nmGe / 211nmZnS / 667.6nmGe is used as the base. As verified by the subsequent test process, the accompanying plated sheet of the zinc selenide substrate together with the film system containing the DLC film layer on the corresponding surface (i.e., the dielectric layer plus the DLC film layer) can not only achieve an average single-sided transmittance of more than 77.5% (specifically 77.81%) in the 8-12μm band, but also pass the blister test, salt spray test, adhesion test, hot and cold shock test, constant temperature and humidity test, constant temperature and humidity test, friction resistance test (moderate friction test), low temperature test and high temperature test, so as to meet the use of the window sheet in various harsh environments and meet the requirements of the application end.
[0024] The cleaning in step S1 is beneficial to improving the surface state of the surface of the lens that needs to be coated with the DLC film layer, and is helpful to improve the bonding performance between the film system (i.e., the dielectric layer plus the DLC film layer) on the surface and the surface of the lens. For example, in step S1, ultrasonic cleaning is used for cleaning. Specifically, ultrasonic cleaning uses aluminum oxide polishing liquid for polishing, followed by ultrasonic pure water cleaning. For example, the aluminum oxide polishing liquid uses a 0.1 μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
[0025] In step S1 , for example, the thickness of the accompanying plating sheet is 2 mm.
[0026] The temperature setting of the vacuum coating machine in step S2 heats the lens through the cavity of the coating machine, which helps the film layer of the dielectric layer grow from the lens and reduces the film layer growth stress. In step S2, for example, the vacuum coating is Siwork ZZS-1350.
[0027] The ion source cleaning in step S3 and step S8 will remove the impurities and oil molecules adsorbed on the surface of the corresponding surface of the lens, thereby greatly improving the interface state, which is helpful to improve the bonding performance between the film layer and the corresponding surface of the lens. At the same time, cleaning by the ion source can heat the corresponding surface of the lens, which is helpful for the growth of the film layer from the lens and reduces the growth stress of the film layer. In step S3, in one example, the anode current of the Hall ion source is 1.2A and the neutralization current is 1.5A.
[0028] In step S4, in one example, when coating the Ge film layer, the Hall ion source parameters are: neutralization current of 1A, neutralization flow rate of 8sccm, anode voltage of 150V, anode current of 1.3A, and argon flow rate of 100%; when coating the ZnS film layer, the Hall ion source parameters are: neutralization current of 0.5A, neutralization flow rate of 8sccm, anode voltage of 100V, anode current of 1A, and argon flow rate of 100%.
[0029] In step S4 and step S9, for example, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned (i.e., the Hall ion source cleaning of step S3 and the RF ion source cleaning of step S8), the crystal controller controls the corresponding operation of the new crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.99 MHz.
[0030] In step S6, for example, the smoothness of the dielectric layer of the product is detected as no dots, scratches or marks on the surface of the dielectric layer of the product are found by naked eyes.
[0031] In step S7, for example, the carbon film machine is a Seawork HLWT700-VII.
[0032] In step S8 , the power of the RF ion source is 650 W, for example.
[0033] [test]
[0034] Example 1
[0035] The preparation method of the DLC film layer plated on the zinc selenide substrate of Example 1 adopts the following steps:
[0036] S1. Before plating, the accompanying plating sheet of the zinc selenide substrate of the lens and the surface of the product that needs to be plated with DLC film are cleaned by ultrasonic cleaning. The thickness of the accompanying plating sheet is 2mm. Ultrasonic cleaning is polished with aluminum oxide polishing liquid, and then ultrasonic pure water cleaning is performed. The aluminum oxide polishing liquid uses 0.1μm polycrystalline diamond liquid from Nanjing Henry Precision Optics Co., Ltd.;
[0037] S2, put the cleaned lens into the fixture, and hang the fixture with the lens into the cavity of the vacuum coating machine. The temperature of the cavity is set to 130℃, and the vacuum coating is Siwork ZZS-1350;
[0038] S3, vacuum coating machine starts, vacuumizes and heats the cavity, and the vacuum degree reaches 1.5×10 -3 When the temperature of the chamber reaches the set temperature, the Hall ion source of the vacuum coating machine is turned on for cleaning. The cleaning time is 6 minutes. The anode voltage of the Hall ion source is 220V, the anode current is 1.2A, the neutralization current is 1.5A, the neutralization gas flow rate is 10sccm, and the argon gas flow rate accounts for 100%;
[0039] S4, vacuum degree reaches 1.0×10 -3 When the DLC film layer is deposited on the surface of the lens where the DLC film layer is required, a dielectric layer composed of 251nmGe / 211nmZnS / 667.6nmGe is deposited in sequence, wherein the numbers with nm before Ge and ZnS are the thicknesses of the corresponding film layers, the Ge film layer is evaporated by electron beam, the ZnS film layer is evaporated by resistance heating, the deposition rate of the Ge film layer is 0.4nm / s, the deposition rate of the ZnS film layer is 0.6nm / s, and each film layer of the dielectric layer is deposited by ion source assisted deposition and is deposited at the set temperature of the chamber;
[0040] In step S4,
[0041] When depositing the Ge film layer, the parameters of the Hall ion source are: neutralization current is 1A, neutralization flow rate is 8sccm, anode voltage is 150V, anode current is 1.3A, and argon flow rate accounts for 100%;
[0042] When depositing the ZnS film, the parameters of the Hall ion source are: neutralization current of 0.5A, neutralization flow rate of 8sccm, anode voltage of 100V, anode current of 1A, and argon flow rate of 100%;
[0043] S5, after the dielectric layer is plated, the cavity is naturally cooled to 80°C, and the fixture and the lens are taken out;
[0044] S6, taking out the lens coated with the dielectric layer and inspecting the smoothness of the dielectric layer of the product. The smoothness of the dielectric layer of the product is detected as follows: no dots, scratches or marks are found on the surface of the dielectric layer of the product by naked eyes;
[0045] S7, place the accompanying plating sheet and the products that have passed the surface finish test with the dielectric layer facing upward on the bottom plate of the carbon film machine, the carbon film machine is the West Work HLWT700-VII;
[0046] S8, carbon film machine vacuum reaches 1.2×10 -3 At Pa, the carbon film machine starts to clean the RF ion source, the cleaning time is 3 min, the argon flow rate of the RF ion source is 20 sccm, and the power is 650 W;
[0047] S9, carbon film machine vacuum reaches 8.0×10 -4 Pa began to deposit the DLC film, the methane gas flow rate was 160sccm, the argon gas flow rate was 10sccm, the RF power was 1000W, the deposition time was 3800s, and the thickness of the DLC film was 1200nm;
[0048] S10, after the DLC film coating is completed, the carbon film machine is cooled for 55 minutes, and the door is opened to take out the lens.
[0049] Figure 2 It is a transmittance curve diagram of the accompanying coating sheet of Example 1 together with the dielectric layer and the DLC film layer on the corresponding surface in the 8-12 μm band. Figure 3 The product of Example 1 is accompanied by a photo of the dielectric layer and the DLC film layer on the corresponding surface. Figure 2 It can be seen that the single-side transmittance of the accompanying coating sheet of Example 1 together with the dielectric layer and the DLC film layer on the corresponding surface in the 8-12 μm band is above 77.5% (specifically 77.81%) on average.
[0050] The accompanying plating sheet of Example 1 together with the dielectric film and the DLC film layer on the corresponding surface (ie, the dielectric film and the DLC film layer as a whole are referred to as a film system) were subjected to the following tests.
[0051] Water bubble test: Take tap water to carry out water bubble test for 2 hours, no film system on the side of the accompanying plating sheet is found to fall off from the accompanying plating sheet, and no film system on the side is found to be cracked.
[0052] Salt spray test: After 48 hours of neutral salt spray test, no film peeling or cracking of the film on the side of the accompanying plating sheet was found.
[0053] Adhesion test: Use hand to stick 3M tape on the side of the accompanying plating sheet and pull the tape along the side in the direction opposite to the sticking end. The film layer on the side of the accompanying plating sheet is not pulled up.
[0054] Thermal shock test: In a high and low temperature box, thermal shock was carried out in the range of -40℃ to 85℃ for 24 hours. No film peeling or cracking of the film on the side of the accompanying plating sheet was found.
[0055] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 48 hours, no film peeling or cracking of the film on the side of the accompanying plating sheet was found.
[0056] Friction resistance test (moderate friction test): Wrap the rubber friction head of the friction machine with degreased cloth, apply a pressure of 4.9N on the film surface of the accompanying plating sheet and rub it 50 times (25 times back and forth). No scratches or damage were found on the film surface of the accompanying plating sheet.
[0057] Low temperature test: in a low temperature box, at -40℃ for 48h, no film peeling or cracking of the film on the side of the accompanying plating sheet was found.
[0058] High temperature test: in a high temperature box, at 85℃ for 48h, no film peeling or cracking of the film on the side of the accompanying plating sheet was found.
[0059] That is, the accompanying plating sheet of Example 1 together with the dielectric film and the DLC film layer on the corresponding surface (that is, the dielectric film and the DLC film layer as a whole are referred to as a film system) all passed the above eight tests.
[0060] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A method for preparing a DLC film layer plated on a zinc selenide substrate, characterized in that: Includes steps: S1, before plating, clean the accompanying plating sheet as the zinc selenide substrate of the lens and the surface of the product that needs to be plated with DLC film; S2, put the cleaned lens into the fixture, and hang the fixture with the lens into the cavity of the vacuum coating machine, and set the temperature of the cavity to 130℃; S3, vacuum coating machine starts, vacuumizes and heats the cavity, and the vacuum degree reaches 1.5×10 -3 Pa and the temperature of the chamber reaches the set temperature, turn on the Hall ion source of the vacuum coating machine for cleaning. The cleaning time is 6 minutes. The anode voltage of the Hall ion source is 220V, the anode current is 1.2-1.5A, the neutralization current is 1.3-1.5A, the neutralization gas flow rate is 10sccm, and the argon gas flow rate accounts for 100%; S4, vacuum degree reaches 1.0×10 -3 When the DLC film layer is deposited on the surface of the lens where the DLC film layer is required, a dielectric layer composed of 251nmGe / 211nmZnS / 667.6nmGe is deposited in sequence, wherein the numbers with nm before Ge and ZnS are the thicknesses of the corresponding film layers, the Ge film layer is evaporated by electron beam, the ZnS film layer is evaporated by resistance heating, the deposition rate of the Ge film layer is 0.4nm / s, the deposition rate of the ZnS film layer is 0.6nm / s, and each film layer of the dielectric layer is deposited by ion source assisted deposition and is deposited at the set temperature of the chamber; S5, after the dielectric layer is plated, the cavity is naturally cooled to below 80°C, and the fixture and the lens are taken out; S6, take out the lens coated with the dielectric layer and check the smoothness of the dielectric layer of the product; S7, placing the accompanying plating sheet and the products that have passed the surface finish inspection on the bottom plate of the carbon film machine with the dielectric layer facing upward; S8, carbon film machine vacuum reaches 1.2×10 -3 Pa, the carbon film machine starts to clean the RF ion source, the cleaning time is 3min, the argon flow rate of the RF ion source is 20sccm, and the power is 600-700W; S9, carbon film machine vacuum reaches 8.0×10 -4 Pa began to deposit the DLC film, the methane gas flow rate was 160sccm, the argon gas flow rate was 10sccm, the RF power was 1000W, the deposition time was 3800s, and the thickness of the DLC film was 1200nm; S10, after the DLC film coating is completed, the carbon film machine is cooled for 50-60 minutes, and the door is opened to take out the lens.
2. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 1, characterized in that: In step S1, ultrasonic cleaning is used for cleaning.
3. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 2, characterized in that: Ultrasonic cleaning uses aluminum oxide polishing liquid for polishing, followed by ultrasonic pure water cleaning. The alumina polishing liquid adopts the 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
4. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 1, characterized in that: In step S1, the thickness of the accompanying plating sheet is 2 mm.
5. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 1, characterized in that: In step S2, the vacuum coating is Siwork ZZS-1350.
6. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 1, characterized in that: In step S3, the anode current of the Hall ion source is 1.2A and the neutralization current is 1.5A.
7. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 1, characterized in that: In step S4, When depositing the Ge film layer, the parameters of the Hall ion source are: neutralization current is 1A, neutralization flow rate is 8sccm, anode voltage is 150V, anode current is 1.3A, and argon flow rate accounts for 100%; When the ZnS film is deposited, the parameters of the Hall ion source are: neutralization current of 0.5 A, neutralization flow rate of 8 sccm, anode voltage of 100 V, anode current of 1 A, and argon flow rate of 100%.
8. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 1, characterized in that: In step S4 and step S9, The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.99MHz.
9. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 1, characterized in that: In step S6, the smoothness of the dielectric layer of the product is detected as follows: no dots, scratches or marks are found on the surface of the dielectric layer of the product by naked eyes.
10. The method for preparing a DLC film layer plated on a zinc selenide substrate according to claim 1, characterized in that: In step S7, the carbon film machine is a Seawork HLWT700-VII.